الانفتاح الدلالي في الخطاب الشعري الحدیث (اللیل انموذجاً) (Journal of the College of Education for Women, 2019)
This research deals with the idea of how the poetic reading can be arich field for producing the potential meanings in each text, through observingthe connection of the words and their link with other, thus composes, from thecollection of these interlaced meanings, what is called the poetic significant(Symbolic) elaboration which deals with the reader of the text by regardinghim as a producer not as a consumer who can read a conscious reading, andbe diligent to solve the problem of the links of the relations among theinspiring words because the language of poetry is an inspired language whichis capable of diversity and multiplicity of readings which is called the Symbolicelaboration.